?A SOLVENT-ExTRACTION STUDY OF THE THERMODYNAMICS OF m-IODOANILINE AND THE PROTON IONIZATION OF THE m-IODOANILINIUM ION (Biological Sciences - PJSIR, 1999)
The distribution coefficients ofm-iodoanilinebetween a petroleumether fraction and aqueous sodium chloride solu- tions were determined at different temperatures. The activity coefficients of the amine in aqueous sodium chloride solutions, and the salting coefficients were determined at different temperatures. The results conformed with the Debye theory of salt effects. The proton ionization constant in terms of molalities (Km), the thermodynamic proton ionization constantoftheaminiumion(Ko)'thebasicdissociationconstantoftheamine(Kb)m,thebasicdissociation constantofthe amineinpurewater(Kb)o'thestandardfreeenergychangeAGo,thestandardenthalpychange e+l", and the standard entropy change ASowereevaluated for the proton ionizationor them-iodoanilinium ion.